Release kinetic model and antimicrobial activity of an innovative minocycline and voriconazole co-delivery system - Zegre, Miguel (2021)
Purpose and Strategy: Development of a new local drug-delivery system aiming at bone infection and the modulation of the polymicrobial activity; simultaneous delivery of minocycline and voriconazole, antibacterial and antifungal agents, respectively; polylactide (PDLLA) scaffolds functionalized with collagen and bioglass, osteogenic enhancers.